Research Trends on Nutrient Management From Digestates Assessed Using a Bibliometric Approach - Magrí, Albert (Frontiers in Sustainable Food Systems, 2018)
Anaerobic digestion is often applied for biological conversion and valorization of organic waste, waste water and other biomass sources as renewable energy and biofuel in the form of biomethane. Composition of the material remaining after digestion, or digestate, is highly dependent on processed feedstocks. This by-product is usually rich in nutrients such as nitrogen and phosphorus, so it is potentially reusable as fertilizer or nutritive broth in agricultural systems. Alternatively, the digestate may need post-treatment based on nutrient removal or recovery strategies. The use of life-cycle assessment tools is becoming popular to analyze nutrient handling scenarios. This study reviews, through a bibliometric-based approach, the research outputs and global trends in the area of knowledge of nutrient management from digestates in the last 30 years, 2017 included. Documentary production followed an upward trend, with a relative productivity in the last three years greater than 37% of the total number of appeared publications. China, USA and Spain were the three most prolific countries. The particular interest in nutrient management alternatives and its evolution were identified. Trends for promoting sustainability include low environmental impact, holistic agro-energy solutions, reduced consumption of resources during digestate processing, and circular economy scenarios based on concepts such as (bio)refinery and recovery of valuable and marketable products.